The “Migration” of Terrorist Actors in Indonesia: From Male-Dominated Terrorist to the Emergence of Female Terrorist Migrant Domestic Workers - Muhammad Subhan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The ISIS group’s declaration in 2014, has inspired female extremists from various countries to join the terrorist group. At the end of 2016, two women were arrested by the Indonesian police for planning terror attacks in two different places. Both are former migrant domestic workers who returned from Hong Kong. This article investigates why women join terrorist groups, why male-dominated terrorist groups recruit women and what makes female migrant domestic workers who return to Indonesia as extremists willing to make a significant contribution to the terrorism movement in Indonesia. This research’s data collection technique is qualitative data collection, and document-based research through literature studies. This article utilizes Quintan Wiktorowicz’s three radicalisation concept phases: cognitive opening, religious seeking and socialisation. This study found that at least four reasons women become extremists, namely personal complaints, influence from family, relatives or lovers, ideological perceptions, and media use, facilitate the radicalisation process. Furthermore, strategic interests seem to be the answer to why terror groups involve women to achieve their goals. The acceptance of terrorist groups to involve women can be the reason why women migrant domestic workers are willing to make an immense contribution to terrorist groups. Their enthusiasm, financial capacity and international experience are expected to strengthen the terror movement in Indonesia. Both create a “mutually reinforcing” relationship that benefits both parties. Further research is needed with a sample of ordinary female extremists outside migrant domestic workers as a comparison to examine women’s motivations and group decisions to include these women in terrorist activities.